Frecuencia de hongos anemófilos productores de micotoxinas en algunos mercados de Lima. Detección de patulina en manzanas en descomposición - Soriano, Marcela (2002)
In the present investigation we have studied some fungae which produce Mycotoxins. The samples were obtained from markets in the city of Lima during the summer, autumn and spring of 1999. The method used was the expositión of the samples in agar-potatoe-dextrose and cloranfenical media. We were able to isolate eleven varieties of fungae which produce mycotoxins such as Penicillium, Aspergillus Fusarium, Altemaria, Cephalosporium, Cladosporium, Paecylomices, Phytomices, Stachybotris, Trichoderma, Trichotecium (Fig. 1,2, 3). The mast frequent ane were the ones of Penicillium gender, which were observed in the following matkets: Huamantanga, Puente de Piedra, Comas, La Victoria y San Luis (Mercado de fruta) In these we got 36 rotten apples in each one af them. The mycotoxill Patulin was identified qualitatively by thin layer chromatography. Besides, we analyzed six samples of apple juice in two of which we observed a positive reaction to the investigation of Patulin. For these assays we used as standard Patulin from Sigma laboratory.